The Colombian transitional process: comparative perspectives on violence against indigenous women - Acosta, Mónica (International journal of transitional justice, 2018)
Colombia has a comprehensive system of truth, justice and reparation stemming from its history with the justice and peace process and its most recent peace agreement. Although indigenous women are the most affected before, during and after conflict, their participation is marginalized within this political context. This article discusses how Colombian transitional justice can be reconfigured when indigenous women’s practices and knowledge travel ‘from the margins’ to the center. We seek to demonstrate how these practices legitimize gender and other types of violence in the name of tradition and also how indigenous women’s experiences go beyond the gendered perspective of violence as a ‘weapon of war.’ Working within the context of the peace process, we gathered data through learning and teaching techniques with indigenous women in three indigenous contexts (Sierra, Pan-Amazon region and Chocó). Our focus is on the interaction between local transitional justice practices and the violence against indigenous women, their resistance practices and the peacebuilding agendas used to implement transitional justice in Colombia.